DEVELOPMENT OF COGNITIVE IDEOLOGICAL RESISTANCE IN YOUTH THROUGH NATIONAL EDUCATION IN THE CONDITIONS OF NEURODIGITAL CIVILIZATION (Universal International Scientific Journal, 2026)
The role and importance of national education in the context of neurodigital civilization, when the minds of young people are increasingly influenced by a powerful flow of information, digital technologies, and global ideological influences, is analyzed. The main goal of the study is to identify effective mechanisms for the formation of cognitive-ideological resistance in young people based on national values, traditions, and spiritual heritage.
Keywords: cognitive resistance, ideological immunity, information security, digital culture, critical thinking skills, youth socialization.